A practical guide to critical thinking : deciding what to do and believe - Hunter, David A., 1965- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
A thoroughly updated introduction to the concepts, methods, and standards of critical thinking, this edition is a unique presentation of the formal strategies used when thinking through reasons and arguments in many areas of expertise. Pursuing an interdisciplinary approach to critical thinking, the book offers a broad conception of critical thinking and explores the practical relevance to conducting research across fields such as business, education and biological sciences. Featuring exercises for a wide range of subject areas, it also includes: real-world examples from many fields of research, which reflect the applicability of critical thinking in everyday life; new topical coverage, including the nature of reasons, assertion and supposing, narrow and broad definitions, circumstantial reasons, and reasoning about causal claims; and selected answers to various exercises to provide readers with instantaneous feedback to support and extend the lessons. --
6.1 REASONING BY PERFECT ANALOGY6.2 IS REASONING BY PERFECT ANALOGY VALID?; 6.3 WHEN IS AN ANALOGICAL CLAIM TRUE OR ACCEPTABLE?; 6.4 REASONING USING REPRESENTATIONAL ANALOGY; 6.5 REASONING WITH SAMPLES; 6.6 WHEN ARE SAMPLES REPRESENTATIVE?; 6.7 REASONING WITH MODELS AND MAPS; 7 Critical Thinking in Action; 7.1 Thinking Critically About a Discipline; 7.2 Identifying a Discipline's Sources of Evidence; 7.3 Identifying a Discipline's Forms of Reasoning; 7.4 Critical-Thinking Questions; 7.5 Thinking Critically in Your Own Decision Making; 7.6 Thinking Critically in Discussion
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Critical thinking; Electronic books